The Effects of Prize Spread and Noise in Elimination Tournaments: A Natural Field Experiment - Delfgaauw, Josse; Dur, Robert; Non, Arjan; Verbeke, Willem (Journal of Labor Economics, 2015)
We conduct a natural field experiment in a retail chain to test predictions of tournament theory regarding prize spread and noise. A random subset of the 208 stores participates in two-stage elimination tournaments. Tournaments differ in the distribution of prize money across winners of the first and second rounds of the tournament. As predicted, we find that a more convex prize spread increases second-round performance at the expense of first-round performance, although the magnitude of these effects is small. Moreover, the treatment effect is larger for stores with more stable past performance.